2010
DOI: 10.1116/1.3268503
|View full text |Cite
|
Sign up to set email alerts
|

Low-dimensional oxide nanostructures on metals: Hybrid systems with novel properties

Abstract: Oxide nanostructures in low dimensions on well-defined metal surfaces form novel hybrid systems with tremendous potential and impact in fundamental research and for the emerging nanotechnologies. In contrast to bulk materials low-dimensional oxide nanostructures not only involve a large number of undercoordinated atoms but their interaction with the metal substrate also provides constraints on their structure and morphology and often yields elastic strain and/or uncompensated charge. These factors modify signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
87
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 148 publications
0
87
0
Order By: Relevance
“…Moreover, if an atomically thin insulating oxide layer covers one of the metals, an electronic interaction can still be operative due to direct electron tunneling depending on the work function difference between the two metals [6]. This phenomenon can be exploited in heterogeneous catalysis to finely adjust and highly improve the catalytic performance of nanoparticles [5,6,13,14] and also for making nanosized metal-insulator-metal (MIM) rectifiers which are critical components in promising high-efficiency light energy harvesting devices where they are called rectifying antenna, or rectenna [15]. The formation of a stable, atomically thin, homogeneous insulator layer with a constant thickness is a critical issue in the operation of nanosized MIM structures [16].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, if an atomically thin insulating oxide layer covers one of the metals, an electronic interaction can still be operative due to direct electron tunneling depending on the work function difference between the two metals [6]. This phenomenon can be exploited in heterogeneous catalysis to finely adjust and highly improve the catalytic performance of nanoparticles [5,6,13,14] and also for making nanosized metal-insulator-metal (MIM) rectifiers which are critical components in promising high-efficiency light energy harvesting devices where they are called rectifying antenna, or rectenna [15]. The formation of a stable, atomically thin, homogeneous insulator layer with a constant thickness is a critical issue in the operation of nanosized MIM structures [16].…”
Section: Introductionmentioning
confidence: 98%
“…The properties of well-characterized metal/oxide model systems are documented in excellent reviews [1][2][3]. The growth of well-defined ultrathin oxide films and their application as template for metal particle growth attracted broad interest and was surveyed in [4][5][6]. The titania oxide support, being of great practical importance, is one of the most studied materials [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, oxide nanostructures of monolayer thickness are often observed on metal surfaces ( Figure 1D). 6,7,10,19 The planar surfaces of the inverse model systems allow the employment of surface science techniques to obtain an atomic understanding of the structureÀreactivity relationship. It has been found that the atomic structure and electronic states of the metal-supported oxides are different from those of their bulk counterparts, resulting in new chemical properties.…”
Section: Oxide-on-metal Inverse Catalystsmentioning
confidence: 99%
“…It has recently been demonstrated that ultra-thin films of transition metal oxides, either formed on a metal surface in an oxygen ambient or epitaxially grown on a different metal support, may exhibit interesting catalytic properties [1][2][3][4][5]. In particular, Ru-oxide films on Ru(0001) [6][7][8] and oxide films on Pt(111) [9][10][11] show a higher CO oxidation rate at nearatmospheric pressures and low temperatures at which pure metals are essentially inactive.…”
Section: Introductionmentioning
confidence: 99%